Policy Statement on IMF Technical Assistance. (International Monetary Fund, 2001)
This chapter presents policy statement on IMF technical assistance (TA) programs. The TA programs provide a cooperative framework for the sharing of knowledge and international experience, in a lasting manner, with member countries. The IMF seeks to provide technical assistance as efficiently and effectively as possible in its core substantive areas of competency namely macroeconomic policy formulation and management among others. Technical assistance is provided in a variety of forms. These include IMF staff missions from headquarters; the placement of experts for periods ranging from a few months to a few years. Technical assistance is provided only when requested by a country's authorities. Since the demand for such assistance normally exceeds the resources available from the IMF, a number of considerations are considered in prioritizing country requests. The IMF encourages member countries who have not yet done so to consider providing such complementary financial support to enhance the resources available for technical assistance, preferably in a manner that is as unrestricted as possible.